Dispute resolutions in Islamic banking: issues and challenges - Omoola, Sodiq Olalekan (2019)
What we will Learn. • Introduction –Banking vs Financing • Introduction – Etymology of Banking Dispute • Islamic Banking Services and Products • Mechanism for Banking Dispute Resolution • Dispute Resolution in Islamic Law Sulh – Qada and Tahkim • Types of Islamic Banking Disputes • Islamic Banking Dispute Resolution in OFS